Assessing the Impact of Celebrity Endorsements on Consumers’ Choices in Southwest Nigeria's Food and Beverage Sector (UNIZIK Journal of Marketing, 2024)
This research investigates the effectiveness of celebrity endorsements in influencing consumer’s Choices in Southwest Nigeria's Food and Beverage Sector. This research employs a quantitative survey methodology to analyse data from a sample of 300 Nigerian consumers, selected through random sampling. Leveraging existing literature, the study explores key factors contributing to successful celebrity endorsements, including perceived authenticity, expertise, and brand-celebrity congruence. The analysis further examines the impact of consumer demographics and cultural influences on endorsement effectiveness. Findings indicate that celebrity endorsements have a minor influence on consumer perceptions of food and beverages in Southwest Nigeria. Nevertheless, while celebrity endorsements can play a minor role in influencing brand perceptions, is not statistically significant in the Nigerian market. The research highlights the need for a nuanced approach to celebrity endorsements, emphasizing the importance of authenticity, brand fit, and integration within a broader marketing strategy
Keywords: celebrity endorsement; brand loyalty; consumer behaviour; marketing strategy; cultural influences; Nigeria